Evaluation of Alexithymia Level in Children With Cystic Fibrosis - Fatih Ercan; Sevgi Pekcan; Semih Erden; Nefise Betül Ercan; Hanife Tuğçe Çağlar; Ahmet Çağlar; Aslı İmran Yılmaz; Gökçen Ünal; Suat Savaş; Fatma Nur Ayman; Hasan Arif İstanbullu; Bahar Ece Tokdemir (Clinical Pediatrics, 2026)
The present study sought to determine the extent of alexithymia within the cystic fibrosis (CF) population and examine how it relates to both the severity of the illness and the effectiveness of patient disease management strategies. The study sample included adolescents aged 14 to 18 years, consisting of individuals with confirmed CF and age-matched healthy controls. Patients with CF exhibited significantly higher total scores on the Toronto Alexithymia Scale (TAS-20) compared to the control group ( P = .013). A significant negative correlation was also observed between TAS-20 scores and forced expiratory volume in 1 second (FEV 1 ) ( P = .005). Pediatric pulmonologists should be aware of alexithymic features when managing CF. For patients who are clinically regressing and have persistent difficulties maintaining adherence to treatment, a multidisciplinary approach that integrates the expertise of pediatric psychiatrists into treatment approaches can overcome both the medical and emotional challenges of CF.